Circulation of Dog Meat for Consumption Purposes in Indonesian Laws and Regulations - Sabrina, Nahdiya (Journal of Asian Multicultural Research for Social Sciences Study, 2023)
The trade in dog meat for consumption has occurred in several places in Indonesia, spread across several cities with special consumers, such as in Medan, Jogjakarta, Bandung, Surakarta, DKI, Manado, Bali. This has attracted public attention, especially animal-loving groups, and has become a national and international concern. Dogs have been slaughtered and consumed by ignoring technical aspects of veterinary public health and animal welfare. The process of cutting dog meat can potentially transmit zoonotic diseases (rabies) and other diseases such as salmonella and ring worm. Several regions in Indonesia have issued regional regulations regarding the prohibition of dog meat distribution. Likewise, there is Law Number 18 of 2009 concerning Animal Husbandry and Health as amended by Law Number 41 of 2014 concerning Amendments to Law Number 18 of 2009 concerning Animal Husbandry and Health; Law Number 18 of 2012 concerning Food; PP No.95/2012 concerning Veterinary Public Health and Animal Welfare, PP No.47/2014 concerning Prevention and Control of Animal Diseases and Circular Letter of the Directorate General of Livestock and Animal Health, Ministry of Agriculture No. 9874/SE/pk.420/F/09/2018 concerning Increasing Supervision of Dog Meat Circulation/Trade. However, in Indonesian law, there are no specific provisions that contain sanctions relating to the capture, trade, slaughter or consumption of dog meat. This study uses normative legal research methods with several approaches, namely the statutory approach and the conceptual approach.